Stable biogas production from single-stage anaerobic digestion of food waste. (1st April 2020) - Shamurad, Burhan; Sallis, Paul; Petropoulos, Evangelos; Tabraiz, Shamas; Ospina, Carolina; Leary, Peter; Dolfing, Jan; Gray, Neil
Highlights: The impact of trace element (TE) & co-digestion on anaerobic digestion was studied. TE is more important than wheat straw-OFMSW co-digestion for stable biogas production. The two strategies had observable effects on microbial communities of the trialled setups. TE stabilises biogas production by sustaining syntrophic partnerships. TE addition will therefore help ensure reliable energy recovery from AD. Abstract: Anaerobic digestion is widely used for the management of the organic fraction of municipal solid waste and is also predicted to play a vital role in the future of renewable energy production. However, reactor instability due to low acid buffering capacity at high organic loading rates in single stage reactors is a known risk of this technology. Such process instability represents a risk to electricity and heat generation through interruptions to biogas production. Co-digestion and trace element supplementation have each been advocated as strategies to stabilize biogas production, but the relative merits of these strategies have never been assessed. Here we operated a series of anaerobic continuously stirred tank reactors fed with synthetic organic household waste with or without trace element supplementation and with or without wheat straw as co-substrate at gradually increasing loading rates. Stable and high methane yields (450–550 mL/g VS) at higher organic loading rates were only maintained with trace element supplementation, regardless of co-digestion. We conclude that trace element supplementation was hierarchically more important than co-digestion at maintaining stable biogas production.